Skip spondylolysis in a javelin thrower: A rare case report - Haranahalli Devendrappa Bharath; Anuj Gupta; Abhishek Srivastava (Indian Spine Journal, 2023)
Pars interarticularis defects leading to spondylolysis and/or spondylolisthesis especially in young athletes are most commonly seen in lower lumbar vertebrae. Conservative treatment with abstinence from the athletic activities, rest, and physiotherapy marks the primary mode of treatment before going to surgical interventions. We report a 26-year-old patient with chronic lower back pain with antecedent history of athletic activities involving javelin throw. Besides an athletic activity, no other history of trauma existed. Radiologic investigations showed skip level pars lysis at L3 and L5 vertebrae. Patient was treated with only conservative methods, abstinence from sports and physiotherapy. Patient had significant improvement in his symptoms. Long-term proper physiotherapy to strengthen the lower back and abdominal muscles is necessary in order to alleviate the symptoms and to regain athletics. To our knowledge there are no reported cases where we find spondylolysis in upper lumbar vertebrae (L3), which is uncommon, along with most common L5 involvement in a young athletic javelin thrower. We have found only isolated L3/L4/L5 or concurrent L3 and L4 or L4 and L5 pars lysis reported in literature. There are no reported cases in literature on skip level spondylolysis in a single individual. Because of the natural history of the disease, conservative methods of management were aptly advocated and positive outcomes were seen in the follow-up.